2016
DOI: 10.1186/s12868-016-0281-8
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 transgene addition to amyloid precursor protein overexpressing transgenic rats increases amyloid beta 42 levels and results in loss of memory retention

Abstract: BackgroundWe previously reported the production of transgenic rats (APP21 line) that over-express human amyloid precursor protein (APP) containing Swedish and Indiana mutations. In order to generate a better model for Alzheimer’s disease (AD), the APP21 rat line was used to generate double transgenic line that over-expressed Presenilin 1 (PS1) with L166P mutation in addition to APP transgene (APP + PS1 line).ResultsThirty-two double transgenic founders were generated and the ultimate transgenic founder was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…An evaluation of error performance found that APP21 and APP+PS1 rats showed poor memory for the location of the escape box during acquisition, retention, and reversal in the Barnes maze compared with the WT rats. This result is consistent with many spatial learning findings using rodent models of AD [ 18 , 19 , 20 , 21 ], including performance in the Barnes maze [ 9 , 12 , 13 , 14 , 15 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…An evaluation of error performance found that APP21 and APP+PS1 rats showed poor memory for the location of the escape box during acquisition, retention, and reversal in the Barnes maze compared with the WT rats. This result is consistent with many spatial learning findings using rodent models of AD [ 18 , 19 , 20 , 21 ], including performance in the Barnes maze [ 9 , 12 , 13 , 14 , 15 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, surprisingly, the WT animals had significantly longer latencies than APP+PS1 animals during acquisition training and had a tendency towards longer latencies during reversal training. This trend was unexpected because previous studies with these models arrived at the opposite conclusion and found that WT had the shortest latencies and APP+PS1 rats had the longest latencies [ 9 ]. The current finding may have stemmed from differential levels of motivation; it is possible that the WT animals were no longer sufficiently aversively stimulated by the Barnes maze environment and thus unmotivated to complete the maze.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The APP+PS1 rat expressing human APP with Swedish and Indiana mutations and human PS1 with L166P mutation was generated by injecting a lentiviral vector containing PSEN1 into the fertilized egg of homozygous APP21 rats [113]. Compared to APP21 rats, APP+PS1 rats had approximately two times the level of Aβ and more severe amyloid pathology, as well as memory and learning deficits that resembled AD [113]. At 10 months, APP+PS1 rats displayed cognitive declines in various areas such as acquisition, retention, and reversal phase as shown in the Barnes maze task [113].…”
Section: App+ps1 Ratmentioning
confidence: 99%